2014
DOI: 10.1088/0741-3335/56/6/064006
|View full text |Cite
|
Sign up to set email alerts
|

Flux rope evolution in interplanetary coronal mass ejections: the 13 May 2005 event

Abstract: Coronal mass ejections (CMEs) are a dramatic manifestation of solar activity that release vast amounts of plasma into the heliosphere, and have many effects on the interplanetary medium and on planetary atmospheres, and are the major driver of space weather. CMEs occur with the formation and expulsion of large-scale magnetic flux ropes from the solar corona, which are routinely observed in interplanetary space. Simulating and predicting the structure and dynamics of these interplanetary CME magnetic fields are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 52 publications
1
46
0
Order By: Relevance
“…Here, 14% of the total flux is lost during the first hour after initiation followed by additional 6% loss as the ICME propagates to 1 AU. A more extreme example of CME-IMF reconnection is found in the simulation of the 15 May 2005 ICME (Manchester et al 2014a) where the poloidal field of the ejected rope is in the opposite direction of the surrounding streamer belt. Figure 15b provides a global view of the reconnection between the MC and the IMF occurring primarily at the north and south extremities of the flux rope.…”
Section: Flux Rope Erosionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, 14% of the total flux is lost during the first hour after initiation followed by additional 6% loss as the ICME propagates to 1 AU. A more extreme example of CME-IMF reconnection is found in the simulation of the 15 May 2005 ICME (Manchester et al 2014a) where the poloidal field of the ejected rope is in the opposite direction of the surrounding streamer belt. Figure 15b provides a global view of the reconnection between the MC and the IMF occurring primarily at the north and south extremities of the flux rope.…”
Section: Flux Rope Erosionmentioning
confidence: 99%
“…Flux ropes ejected from the solar corona during CMEs may travel through interplanetary space largely intact, and careful examination suggests that they can be connected to the magnetic structures observed at 1 AU (e.g., Yurchyshyn et al 2007;Démoulin 2008;Möstl et al 2008;Liu et al 2010aLiu et al ,b, 2011Howard and DeForest 2012;Manchester et al 2014a;. The magnetic fields associated with ICMEs often retain a coherent structure resembling a flux rope.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the intensity of the geomagnetic storms, as well as the ICMEs' Sun-Earth transit times, were mainly governed by the parameters of their solar sources, such as the total unsigned magnetic flux at the photospheric level within the post-eruption EUV arcades and dimming regions. For example, the magnetic fluxes in the solar sources of the strongest geomagnetic storms in cycle 23 (Dst < −200 nT, the near-Earth magnetic field |B| > 50 nT, and large southern B z component) such as the 14-15 July 2000, 22-24 November 2001, 28-30 October 2003, and 13-15 May 2005superstorms (see, e.g., Wu et al, 2005Cerrato et al, 2012;Manchester, van der Holst, and Lavraud, 2014) were very large, (240 − 870) × 10 20 Mx (maxwell). The severity of the geomagnetic superstorm of 20 November 2003 appears to correspond to the near-Earth magnetic field of |B| max ≈ 56 nT with a large southward component up to B z ≈ −45 nT, while the total unsigned magnetic flux in the eruption region was as low as 130 × 10 20 Mx, even including the flare arcade in AR 10501 and all dimming regions.…”
Section: Introductionmentioning
confidence: 99%